Therapeutic potential of nanoemulsions as feasible wagons for targeting Alzheimer's disease. Issue 12 (December 2021) - Handa, Mayank; Tiwari, Sanjay; Yadav, Awesh K.; Almalki, Waleed H.; Alghamdi, Saad; Alharbi, Khalid S.; Shukla, Rahul; Beg, Sarwar
Highlights: Blood-brain barrier is responsible for reduced therapeutic efficacy of drugs. Literature reports demonstrate excellent ability of nanocarriers in brain delivery. Nanoemulsion are therapeutically effective for drug delivery in Alzheimer's disease. Use of effective drug targeting modalities to brain is the need of the hour. Abstract: Alzheimer's disease (AD) is an irreversible dementia state with characteristic clinical manifestations, including declining cognitive skills and loss of memory, which particularly affects the older population. Despite significant efforts in the field of nano-based drug delivery, there have been few successes achieved in the design of a rational drug therapy. Nanoemulsions (NEs) have potential for the delivery of AD therapeutics owing to their capability for brain drug delivery. Still, there is a long way to go before such therapeutics become a reality in the clinic. In this review, we highlight the preclinical assessment of NEs for AD and discuss the regulatory constraints to their clinical acceptance.